Dynamic causal modelling of auditory surprise during disconnected consciousness: The role of feedback connectivity - Casey, Cameron P.; Tanabe, Sean; Farahbakhsh, Zahra; Parker, Margaret; Bo, Amber; White, Marissa; Ballweg, Tyler; Mcintosh, Andrew; Filbey, William; Banks, Matthew I.; Saalmann, Yuri B.; Pearce, Robert A.; et al. (NeuroImage (Orlando, Fla.), 2022)
The neural mechanisms through which individuals lose sensory awareness of their environment during anesthesia remains poorly understood despite being of vital importance to the field. Prior research has not distinguished between sensory awareness of the environment (connectedness) and consciousness itself. In the current study, we investigated the neural correlates of sensory awareness by contrasting neural responses to an auditory roving oddball paradigm during consciousness with sensory awareness (connected consciousness) and consciousness without sensory awareness (disconnected consciousness). These states were captured using a serial awakening paradigm with the sedative alpha2 adrenergic agonist dexmedetomidine, chosen based on our published hypothesis that suppression of noradrenaline signaling is key to induce a state of sensory disconnection. High-density electroencephalography was recorded from 18 human subjects before and after administration of dexmedetomidine. By investigating event-related potentials and taking advantage of advances in Dynamic Causal Modeling (DCM), we assessed alterations in effective connectivity between nodes of a previously established auditory processing network. We found that during disconnected consciousness, the scalp-level response to standard tones produced a P3 response that was absent during connected consciousness. This P3 response resembled the response to oddball tones seen in connected consciousness. DCM showed that disconnection produced increases in standard tone feedback signaling throughout the auditory network. Simulation analyses showed that these changes in connectivity, most notably the increase in feedback from right superior temporal gyrus to right A1, can explain the new P3 response. Together these findings show that during disconnected consciousness there is a disruption of normal predictive coding processes, so that all incoming auditory stimuli become similarly surprising.